Pengaruh Word of Mouth (WoM) dan Keragaman Produk Terhadap Minat Beli pada Toko Rania Hijab di Kota Langsa - Saragih, Yola Amelia; Amilia, Suri; Rahman, Maulana (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
The growth of Muslim fashion in Indonesia serves as the driving force behind this study. The increasing fashion of Muslim women, in particular, is indicative of this trend. This research sought to ascertain how product diversity and word-of-mouth (WoM) affected consumers’ interest in making a purchase at the Rania Hijab Store in Langsa City. All Langsa City residents who have made purchases from the Rania Hijab Store made up the study’s demographic. Purposive sampling was the sample technique used. There were 96 responders in the sample. Multiple linear regression analysis, the t-test, the F-test, and the coefficient of determination test (Adjusted R2) were all used in the data analysis process. Based on the study’s findings, it was determined that both product diversity and word-of-mouth (WoM) significantly influenced purchase interest. The study’s findings may be taken into account to assist store owners in enhancing their offerings and broadening the selection of hijabs to better suit the demands and preferences of their customers.